The Influence of Work Life Balance, Quality of Work Life, and Self-efficacy on Job Satisfaction of Contract Employees of Java Heritage Hotel Purwokerto - Ella Galih Cahyo Sakti Aji; Hermin Endratno; Hengky Widhiandono; Ika Yustina Rahmawati (Indonesian Journal of Business Analytics, 2025)
This study examines the influence of Work Life Balance (WLB), Quality of Work Life (QWL), and Self-efficacy on Job Satisfaction among contract employees at Java Heritage Hotel Purwokerto. Using a quantitative approach and saturated sampling, 107 respondents completed a five-point Likert scale questionnaire. Data were analyzed with Structural Equation Modeling - Partial Least Squares (SEM-PLS) via SmartPLS. Results show that WLB has a negative but insignificant effect on job satisfaction, while QWL and Self-efficacy have significant positive effects. These findings indicate that improving work environment quality and employee confidence plays a crucial role in enhancing job satisfaction. The study offers insights for HR strategies, especially in supporting contract-based employees.